The Transformative Power of RhythmicPlastic Science: Enhancing Performance and Well-being in Actors - pcadmin, Qosbergenov Aqilbek Idirisovich (Global Scientific Publishing, 2025)
This scientific article explores the significance and myriad benefits of incorporating rhythmic-plastic science into the training and practice of actors. Rhythmic-plasticity refers to the malleability and adaptability of biological rhythms, which can be harnessed to enhance cognitive, emotional, and physical capabilities. This interdisciplinary approach draws from neuroscience, psychology, and performing arts, offering actors a unique and effective methodology to elevate their craft. Through the integration of rhythmic-plastic principles, actors can experience improved focus, emotional expressiveness, and overall well-being, ultimately enhancing their performance on stage and screen.
Keywords: Rhythmic-Plastic Science; Actor Training; Biological Rhythms